ARCHITECTURE IN THE PERIOD OF POSTCOLONIALISM - Žilka, Tibor (Porównania, 2015)
In the period of totalitarianism in Central Europe many important architectural monuments were demolished. This trend continues in the post-colonial era, although due to other causes. In Slovakia individuals access the sights very easily, but as their relationship to the artistic value is nonexistent, the architectural heritage is frequently destroyed though it used to have different important functions. This is particularly visible on the examples of the bath house Machnáč (1932) and the pool “Green frog” – Zelená žaba (1937). Maison Machnáč was designed by the architect Jaromir Krejcar from Prague, whereas Green frog by Bohuslav Fuchs, the architect from Brno. Poll Green frog with its unique-ness and artistic level goes beyond Slovakia. Nonetheless, the current owner does not want to restore it to its original condition.